Hypoglycemia: an emergency in the nursing office - Oblitas-Guerrero, Susan Miriam (2022)
In diabetes, episodes of hypoglycemia are often a common complication that requires urgent action to bring the patient's glucose values back within the normal range, otherwise seizures  and nerve damage may occur. Hypoglycemia is defned and classifed  as hypoglycemia: if the glucose value result is less than 70 mg. Then the  15/15 rule should be applied if the  patient remains lucid, awake,  conscious and able to take food or  liquids orally, otherwise, the  administration of glucagon will be  necessary and urgent. We present the case of a 39-year-old male, with a history of 5 years of illness: type2 diabetes mellitus, with NPH insulin treatment every 24 hours for the lasttwo years, who reported that  approximately ten minutes ago he  presented: "dizziness", weakness and "cold", he also manifested an  indescribably strange sensation of "fear", palpitations and profuse  sweating only on the forehead. She then proceeded to the hemoglucose  test with a result of "LO" meaning that  lood glucose is less than 20 mg/dl, a  situation that should be addressed immediately and promptly, negative complications may occur in the patient. This case report has the main  objective of assessing the results of  the glucometer in the nursing ofce and  to be able to make immediate  decisions with nursing interventions  that allow attending to the urgency of  hypoglycemia in the nursing ofce in a  hospital. This situation made it  possible to provide diabetic education  to the patient: identifying the situation  of hypoglycemia, identifcation of its  symptoms, low glucose values,  interventions in a safe and fast way by  offering to take a food such as a candy  or a product containing sugar, for  example: grapes, fruit juices, soft drink  with sugar or a glass of fruit  juice, or half a glass with water and  two spoonfuls of sugar or a spoonful  of honey. Any of these options can be  effective and whatever is more  accessible to the patient. For the  resolution of the case: we proceeded  to serve half a glass of bottled juice in  order to balance the patient's blood  glucose values. The patient's evolution  was favorable, he came out lucid,  awake and returned home normally.